Synthesis and Antimicrobial Effects of 1,3,5-Substituted Phenyl Formazans - Uraz, Guven; Yilmaz, Ebru; Tezcan, Habibe; Porsuk, Nesrin; Imamoglu, Gamze; Savas Kartli, Onur (Asian Journal of Chemistry, 2011)
In this study, novel formazans with various substituents on 1,3,5-phenyl rings were synthesized and their structures were elucidated with the use of elemental analysis, mass, 1H NMR, 13C NMR, IR, UV-VIS spectra. Also, antimicrobial effects of formazans were tested against selected microorganism, Staphylococus aureus, S. epidermidis, S. saprophyticus, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae. Moreover, the antiyeast effects of the formazans are seen on the Candida kefir, C. glabrata, C. tropicalis, Cryptococcus neofarmans, Saccharomyces cerevisiae. In the present study, it was generally observed that the formazans were very active against Candida kefir, C. tropicalis, Cryptococcus neofarmans and Saccharomyces cerevisiae.